PEMBELAJARAN AQIDAH AKHLAK TERHADAP PEMBENTUKAN KARAKTER SOPAN SANTUN SISWA MIS MISHBAHUL AULAD KOTA SUKABUMI - Dadang Sahroni; Irsan Apriandinata; Navisa Rahma; Anisa Fitri; Regita Agustiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education plays an important role in developing individual potential and shaping students’ character, particularly in the context of Islamic education which emphasizes the formation of polite character as a reflection of faith. This study aims to examine the relationship between Aqidah Akhlak learning and the development of students’ polite character in the fourth grade of MIS Mishbahul Aulad, Sukabumi City. This study employed a quantitative approach using an ex post facto method, involving 30 students as research subjects. Data were collected through questionnaires, observations, and interviews. The data were analyzed using validity, reliability, normality, and linearity tests, as well as simple linear regression analysis. The results showed that the research instruments were valid and reliable, the data were normally distributed, and there was a linear relationship between the two variables. However, the regression analysis indicated a significance value of 0.087 > 0.05, meaning that there was no significant relationship between Aqidah Akhlak learning and the development of students’ polite character. Nevertheless, a positive regression coefficient of 0.276 was obtained, with an R Square value of 0.101, indicating a contribution of 10.1%, while the remaining variance was influenced by other factors, both internal (religious understanding, motivation, and self-concept) and external (family, school, and community environment). Thus, Aqidah Akhlak learning still plays a role in supporting the development of students’ polite character, although it does not show a statistically significant relationship. Therefore, it needs to be continuously optimized and contextualized in the learning process.